Pemikiran Ekonomi Ibnu Khaldun dan Relevansinya terhadap Pengembangan Ekonomi Modern - Arivah, Nurul; Ikbal, Muh. (Journal of Islamic Economic Studies, 2025)
Classical Islamic economic thought has made significant contributions to the development of contemporary Islamic economic theory. One of the key figures in this body of thought is Ibn Khaldun, who, through his work, Muqaddimah, put forward holistic economic concepts, encompassing market mechanisms, the relationship between taxes and productivity, the role of the state, and the dynamics of economic cycles. This article aims to analyze Ibn Khaldun's economic thought and its relevance to the development of a modern economy. The research method used is library research with a qualitative-descriptive approach, through analysis of classical literature and scientific research. The results of the study indicate that Ibn Khaldun's thoughts in the context of Social Justice, Fiscal Balance, and the Role of the State in the Economic System are relevant to the development of a modern economy. The study's findings demonstrate that Ibn Khaldun's thoughts on social justice, fiscal balance, and the role of the state in the economic system are relevant to the development of the modern economy. The study's findings demonstrate that Ibn Khaldun's thoughts are strongly relevant to the principles of modern Islamic economics, particularly in the areas of economic justice, market balance, proportional fiscal policy, and ethics in economic activity. These concepts can serve as a theoretical basis for formulating sustainable Islamic economic policies and practices that are oriented toward the welfare of society. Therefore, Ibn Khaldun's thoughts remain relevant and applicable in addressing the challenges of Islamic economics in the contemporary era.